Evaluation of Circulation Service Quality Using Libqual+Tm Method at Library of Universitas Sains dan Teknologi Indonesia - Pratama, Mahendra; Rosman; Noproanto, Eko (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to find out and evaluate the quality of circulation services based on user perceptions, as well as identify service dimensions that need to be maintained, improved, or improved in the library of library of Universitas Sains dan Teknologi Indonesia. By using a quantitative descriptive. The results of the study show that overall, the quality of circulation services at the Library of Universitas Sains dan Teknologi Indonesia is quite good. Nevertheless, there is a gap between the expected services and the services received. The Affect of Service dimension obtained a relatively high score, indicating a fairly satisfactory performance of librarians. Meanwhile, the dimensions of Information Control and Library as Place show results that are still below the expectations of users and it is suggested that the academic library increase the number and quality of human resources in the circulation section, update and add to the collection according to the needs of the study program, and improve facilities and infrastructure, especially the internet network and other service support facilities. This research is expected to be useful to add literature and scientific references related to the evaluation of the quality of library services, especially circulation services using the LibQual+ ™ method approach and can be used as a basis for improving circulation services in the academic library and other universities if they feel that they are experiencing similar things so that they can improve professionalism in providing services.